The complete National Geographic 108 years of National Geographic magazine on CD-ROM - National Geographic Society (U.S.). (Washington, D.C. : National Geographic Interactive ; Novato, CA: Distributed by Mindscape, 1997)
An archive of 108 years of National Geographic magazine. The program begings in 1888, with the very first issue ever published, and includes all issues through 1996.
Volume I. 1888-1909 -- Volume II. 1910s -- Volume III. 1920s -- Volume IV. 1930s -- Volume V. 1940s -- Volume VI. 1950s -- Volume VII. 1960s -- Volume VIII. 1970S -- Volume VIX. 1980s --Volume X. 1990s.
Volume xi.1997.
WINDOWS System requirements: 80486DX 33 MHz processor ; Windows 3.1x running under DOS 6.0 or higher or Windows 95 Version 1 ; 8 MB RAM ; 10 MB free disk space ; VESA standar VGA ; 640 X 480 resolution x 256 colors ; Dual-speed CD-ROM ; optional ; printer (300 dpi or higher)
Macintosh system requirements : 68030 33 MHz processor ; System 7.5 higher ; 8 MB RAM ; 10 MB free disc space ; 640 x 480 resolution x 256 colors; Dual-speed CD-ROM ; optional : printer (300 dpi or higher)
Keywords: National Geographic Society (U.S.).; Geography -- Periodicals -- Interactive multimedia; Interactive multimedia; CD-ROMs.